2018
DOI: 10.3389/fnbeh.2018.00184
|View full text |Cite
|
Sign up to set email alerts
|

Do Individual Differences Influence Moment-by-Moment Reports of Emotion Perceived in Music and Speech Prosody?

Abstract: Comparison of emotion perception in music and prosody has the potential to contribute to an understanding of their speculated shared evolutionary origin. Previous research suggests shared sensitivity to and processing of music and speech, but less is known about how emotion perception in the auditory domain might be influenced by individual differences. Personality, emotional intelligence, gender, musical training and age exert some influence on discrete, summative judgments of perceived emotion in music and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Finally,Waaramaa and Leisiö (2013) investigated the link between musical interests and emotional prosody perception in a large-scale cross-cultural study across five different countries(Estonia, Finland, Russia, Sweden, USA). Musical interests tended to have a positive effect on vocal emotion Musicality and Vocal Emotion Perception 15 identification, but like inDibben et al (2018), this finding was based on very few self-reported items only.…”
mentioning
confidence: 55%
“…Finally,Waaramaa and Leisiö (2013) investigated the link between musical interests and emotional prosody perception in a large-scale cross-cultural study across five different countries(Estonia, Finland, Russia, Sweden, USA). Musical interests tended to have a positive effect on vocal emotion Musicality and Vocal Emotion Perception 15 identification, but like inDibben et al (2018), this finding was based on very few self-reported items only.…”
mentioning
confidence: 55%
“…Performance is measured in terms of the accuracy with which emotions are recognized. There are also studies evaluating other aspects of emotional processing, however, including valence and arousal perception (Dibben et al, 2018), and inferences of distress (Parsons et al, 2014) and depression in voices (Nilsonne & Sundberg, 1985). Trained participants are usually adults with at least five years of classical music training, which is in line with the broader literature on music training (Zhang et al, 2018).…”
Section: Cross-sectional Evidencementioning
confidence: 77%
“…Importantly, there are six studies that failed to find training effects. This was observed for emotional prosody recognition in linguistic stimuli including words, pseudowords, and sentences (Başkent et al, 2018;Dibben et al, 2018;Mualem & Lavidor, 2015;Park et al, 2015;Trimmer & Cuddy, 2008), for tone analogues of spoken sentences (Trimmer & Cuddy, 2008), and for humming voices (Weijkamp & Sadakata, 2016). For instance, Trimmer and Cuddy (2008) tested 100 participants with varying levels of music training, and found that emotion recognition in sentences and tone analogues correlated with emotional intelligence but not with music training.…”
Section: Cross-sectional Evidencementioning
confidence: 92%
See 1 more Smart Citation
“…There is a strong relationship between the recognition of perceived emotions in both speech and music: shared taxonomies of emotion [1], [2], shared biological and evolutionary processes in the brain [3], [4], similar acoustic cues that are related in both domains [5], [6], and models that attempt to recognize perceived emotions across domains [7], [8]. Researchers have evaluated how individual differences influence emotions perceived in music and speech prosody by English speakers [9]. They found that the ratings on speech are unaffected by factors such as personality, musical training, emotional intelligence and gender, but may be influenced by age.…”
Section: Introductionmentioning
confidence: 99%